2021
DOI: 10.1136/annrheumdis-2021-221571
|View full text |Cite
|
Sign up to set email alerts
|

Two-dose COVID-19 vaccination and possible arthritis flare among patients with rheumatoid arthritis in Hong Kong

Abstract: ObjectivesTo investigate the relationship between COVID-19 full vaccination (two completed doses) and possible arthritis flare.MethodsPatients with rheumatoid arthritis (RA) were identified from population-based electronic medical records with vaccination linkage and categorised into BNT162b2 (mRNA vaccine), CoronaVac (inactive virus vaccine) and non-vaccinated groups. The risk of possible arthritis flare after vaccination was compared using a propensity-weighted cohort study design. We defined possible arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 18 publications
6
83
0
1
Order By: Relevance
“…Despite the increased risk of myocarditis and the marginally increased risk of sleeping disturbance/disorder the other AESIs recorded among the vaccinated group were similar to the unvaccinated group. Such observation was consistent with local studies conducted in the adult population [ 16 , 17 ]. Narcolepsy, one of the conditions covered by our definition of sleeping disturbance/disorder, has not been reported in other studies on COVID-19 vaccine-related AESI so far, but reported previously to be possibly associated with influenza vaccination [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the increased risk of myocarditis and the marginally increased risk of sleeping disturbance/disorder the other AESIs recorded among the vaccinated group were similar to the unvaccinated group. Such observation was consistent with local studies conducted in the adult population [ 16 , 17 ]. Narcolepsy, one of the conditions covered by our definition of sleeping disturbance/disorder, has not been reported in other studies on COVID-19 vaccine-related AESI so far, but reported previously to be possibly associated with influenza vaccination [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we removed those who died before the index date, were hospitalized on the index date (in the unvaccinated group) or had any AESI records before the index date. This approach has been used in previous large-scale pharmacovigilance studies as well [ 17 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects of COVID-19 vaccine on IBD activity, particularly severe flare resulting in hospitalisation and the interplay with the use of immunotherapy remain unknown. To address these questions, we analysed the territory-wide electronic medical records with vaccination linkage database in Hong Kong2–7 to examine the association between BNT162b2 vaccination and IBD flare.…”
mentioning
confidence: 99%
“…Prior studies have focused mainly on DMARD changes early in the pandemic related to concerns about drug supply or immunosuppression (32)(33)(34). Other studies have focused on temporary medication changes after COVID-19 vaccination and have found little evidence of increased risk of flare (35)(36)(37)(38). Compared to those studies, participants in our study may have had longer disruption of DMARDs while acutely ill, particularly those who required hospitalization, which may have increased their risk of flare.…”
Section: Discussionmentioning
confidence: 67%